Improved geometric modeling using the method of fundamental solutions. (1st September 2021) - Chen, C.S.; Amuzu, Lionel; Acheampong, Kwesi; Zhu, Huiqing
Abstract: In this paper, we propose a new geometric model that includes a fourth-order partial differential equation (PDE) for reconstructing 2D curves. For instance, we use this model to reproduce letters in Time Roman font. The method of fundamental solutions (MFS), which is a simple and easily implemented meshless method, is employed for solving the proposed PDEs. In addition, no fictitious boundary is required for the proposed MFS formulation, which further simplifies the implementation of the numerical method. Three examples of 2D curve reproduction are presented to demonstrate the effectiveness of the proposed model.